Lip repositioning surgery: A pioneering technique for perio-esthetics - Harpreet Singh Grover; Anil Gupta; Shailly Luthra (Wolters Kluwer Medknow Publications, 2014)
In our esthetic conscious society people are now demanding all types of treatments possible to have a pleasing and attractive personality. A dazzling and beautiful smile can work wonders for anyone's personality. Our smile mirrors our persona, our unique being. However, a beautiful smile comprises of a perfect balance of the white and pink. This imbalance of excessive gingival display (EGD) can be managed by a variety of treatment modalities, depending on accurate diagnosis. This case report demonstrates the successful management of EGD with a lip-repositioning procedure in a patient with incompetent short upper lip. This was accomplished by removing a partial thickness strip of mucosa from the maxillary buccal vestibule and suturing the lip mucosa to the mucogingival line. This resulted in a narrower vestibule and restricted muscle pull, thereby resulting in competent lips and reduced gingival display during smiling.